2020
DOI: 10.1155/2020/2626090
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of eIF2α Dephosphorylation Protects Hepatocytes from Apoptosis by Alleviating ER Stress in Acute Liver Injury

Abstract: Objectives. Protein kinase R-like ER kinase (PERK)/eukaryotic initiation factor 2 alpha (eIF2α) is an important factor along the main pathways for endoplasmic reticulum (ER) stress-mediated apoptosis. In this study, we investigated the effects of eIF2α phosphorylation on hepatocyte apoptosis and the ER stress mechanisms in acute liver injury. Methods. eIF2α phosphorylation and apoptosis under ER stress were monitored and measured in male BALB/c mice with acute liver injury and human hepatocyte line LO2 cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Liver damage is common pathological basis of various liver diseases, and ER stress inevitably appears in liver damage ( Liu et al, 2017 ). It was reported that the suppression of EIF2A alleviated carbon tetrachloride ( CCl4 )-induced liver damage in mice and human hepatocyte cell line LO2 ( Tang et al, 2020 ). Similarly, Borkham-Kamphorst et al found that long-term repetitive injection of CCl 4 aggravated ER stress and UPR then caused liver cell apoptosis in lipocalin 2 null mice ( Borkham-Kamphorst et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Liver damage is common pathological basis of various liver diseases, and ER stress inevitably appears in liver damage ( Liu et al, 2017 ). It was reported that the suppression of EIF2A alleviated carbon tetrachloride ( CCl4 )-induced liver damage in mice and human hepatocyte cell line LO2 ( Tang et al, 2020 ). Similarly, Borkham-Kamphorst et al found that long-term repetitive injection of CCl 4 aggravated ER stress and UPR then caused liver cell apoptosis in lipocalin 2 null mice ( Borkham-Kamphorst et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…ER stress promotes intracellular homeostasis through UPR response, but excessive ER stress activates apoptosis signaling pathways 34 . Simultaneously, ER stress inhibits the overall protein synthesis through PERK/eIF2α signaling and upregulates the expression of molecular chaperones, such as GRP78 through ER stress-related transcription factors, such as ATF6, ATF4, and XBP1 21 . In this study, the expression of ATF4, ATF6, XBP1s, GRP78, and caspase-12 were analyzed to monitor ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of MRP2 controls acute liver injury through a negative feedback mechanism that reduces ER stress. In addition, the inhibition of eIF2α dephosphorylation reduced hepatocyte apoptosis by alleviating ER stress in acute liver injury 21 . In combination, the regulation of ER stress could alleviate the pathological progression of liver injury.…”
Section: Introductionmentioning
confidence: 98%
“…Following 1 week of acclimatization, mice were randomly assigned to model groups (CCl 4 or TM) and solvent control groups (olive oil for CCl 4 or phosphate-buffered saline (PBS) as the TM solvent control). All treatments were administered via the intraperitoneal route, and experimental outcomes were detected at 12, 24, and 48 h postinjection as detailed previously [30,34]. In the CCl 4 group, mice received 1 mL/kg CCl 4 , and mice in the olive oil control group received 4 mL/kg olive oil.…”
Section: Generation Of An Acutementioning
confidence: 99%